Abilities of berberine and chemically modified berberines to inhibit proliferation of pancreatic cancer cells. (January 2019) - Abrams, Stephen L.; Follo, Matilde Y.; Steelman, Linda S.; Lertpiriyapong, Kvin; Cocco, Lucio; Ratti, Stefano; Martelli, Alberto M.; Candido, Saverio; Libra, Massimo; Murata, Ramiro M.; Rosalen, Pedro L.; Montalto, Giuseppe; et al.
Abstract: Berberine (BBR) is a common nutraceutical consumed by millions worldwide. BBR has many different effects on human health, e.g., diabetes, diarrhea, inflammation and now more recently it has been proposed to have potent anti-cancer effects. BBR has been shown to suppress the growth of cancer cells more than normal cells. BBR has been proposed to exert its growth-inhibitory effects by many different biochemical mechanisms including: suppression of cell cycle progression, induction of reactive oxygen species, induction of apoptosis and autophagy and interactions with DNA potentially leading to DNA damage, and altered gene expression. Pancreatic cancer is a leading cancer worldwide associated with a poor prognosis. As our population ages, pancreatic cancer has an increasing incidence and will likely become the second leading cause of death from cancer. There are few truly-effective therapeutic options for pancreatic cancer. Surgery and certain chemotherapeutic drugs are used to treat pancreatic cancer patients. Novel approaches to treat pancreatic cancer patients are direly needed as they usually survive for less than a year after being diagnosed. In the following manuscript, we discuss the abilities of BBR and certain chemically-modified BBRs (NAX compounds) to suppress growth of pancreatic cancer cells.